How do crises spread? The polycrisis and crisis transmission - Malte Brosig (Global Sustainability)
Abstract Non-technical summary The term polycrisis refers to simultaneous and interconnected crises that amplify each other's effects. Understanding how crises spread is crucial for understanding how a polycrisis operates. This article explores the conditions under which crises transmit across systems. By examining various theories – from complexity thinking to epidemiology – it discusses to importance of several conducive conditions and system resilience in shaping crisis transmission. The polycrisis concept underscores the need for interdisciplinary approaches to address interconnected global challenges. By identifying how crises spread, policymakers and researchers can better anticipate and mitigate their impacts, fostering resilience in the face of growing systemic risks.